Skin and Clothes Matching Seeded by Color System Selection - Rahmadi Kurnia; Meza Silvana; Ikhwana Elfitri (Institute of Advanced Engineering and Science, 2015)
This work has designed an automated system to recommend clothe for people based on their skin. Skin colors from various races were relate with a variety of clothing colors to obtain their harmonization value. This research involve 30 respondents through questionnaire to provide initial views to a variety of colors to match the skin color variation. Input from the respondents is then analyzed to choose the right color system to be linked with skin color. To determine the relationship between skin color and clothes color fuzzy logic rules were used. The system was then tested again to 30 respondents. The results showed that variations in skin color and clothing are best on a combination of Cr and Saturation. DOI: http://dx.doi.org/10.11591/telkomnika.v14i1.7235